Corporate Governance Mechanism, Firm Size and Its Effects on Acceptance of Qualified Audit Opinion - Suryandari , Dhini; Andhika, Ega (KnE Social Sciences, 2020)
This study aims to examine the effect of internal and external corporate governance mechanisms that are proxied by the size of the independent commissioners, the audit committee’s educational background, the proportion of institutional ownership, audit quality, and company size factors towards acceptance of qualified audit opinion. The population in this study is the infrastructure, utilities and transportation sectors listed in the Indonesia Stock Exchange in 2013-2017. Based on the purposive sampling method, it obtained 120 analytical units from the sample data. The analysis used in this study is logistic regression analysis. The results of this study found that if the size of the company which calculated based on total assets had a negative influence on the acceptance of qualified audit opinion. On the other hand, the element of Good Corporate Governance in the form of independent commissioners, audit committee, institutional ownership, and audit quality has no effect on the acceptance of qualified audit opinion. The conclusion of this study is the presence of the company’s internal support body are not able to influence the company’s accounting for the better. Keywords: good corporate governance, qualified audit opinion, firm size